Pengembangan Media Dengan Model Ciro Sebagai Evaluasi Program Pembelajaran Ilmu Tajwid di Pesantren Miftahul Mu’arif - Edi Hermanto (Universitas Yudharta Pasuruan, 2021)
This study aims to determine the effectiveness of the development of media development with the Ciro model as an evaluation of the tajwid learning program at Miftahul Mu'arif Kampar Islamic boarding school. This is very important to increase the success rate of conducting media development when learning Tajid reading. The subjects of this survey were principals, Islamic boarding school management teams, and students. Methods of collecting data were questionnaires, observations, interviews, and documentation. The data analysis technique in this research is descriptive quantitative to analyze the percentage level of effectiveness of each component in the Ciro model. The results of the evaluation of media development as an evaluation of the tajwid learning program at Miftahul Mu'arif Islamic boarding school that the effectiveness of media development in Miftahul Mu'arif Islamic boarding school there is a difference in the average pretest and posttest scores of 7.77 with an N-Gain of 0.421, it can be concluded that there is an increase in the average of 5,866 and in the implementation of recitation learning media it is in the very practical category with a practical percentage level of 92.81%.